Does the use of dietary supplements enhance athletes’ sport performances? A systematic review and a meta-analysis (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The consumption of dietary supplements has increased in recent years.Despite their widespread use, there is confusion about effects on sport performances.The aim of this study was to investigate association between use of supplements and enhance of athletes’ sports performance.Methods: A review and a meta-analysis of studies conducted on Dietary Supplements and Sports between 2003 and 2013 were performed. Enhancement on sport performances was considered as outcome. The following aspects related to enhancement were considered: ergogenic effect (EE), time to exhaustion (TTE), muscular endurance (ME), post-exercise recovery (PER) and body mass (BM). With respect to meta-analysis, data on level of post Exercise Glucose (GpE [mg/dL]) and level of post exercise Lactate (LpE [mmol/L]) were considered as  indicators of TTE, PER and EE. Similarly, Change in Body Mass (CBM) [kg] was used as indicator of BM.Results: The most investigated dietary supplements were: Creatine, Carbohydrates, Beta-alanine, Proteins. The qualitative analysis evaluating the effect of supplements on sports listed by the International Olympic Committee has achieved interesting results: supplements didn’t show statistically significant effects when compared to placebo in more than 48% of papers.For the quantitative analysis, 15 studies were considered. The meta-analysis showed that there was no significant effect of Beta-alanine, Creatine and Carbohydrates on LpE and GpE. Furthermore, a non-significant increase in BM was observed in athletes undergoing Creatine compared to placebo.Conclusion: Considering the increasing attention to this topic, it would be interesting to investigate the existing awareness about effectiveness and possible risks of supplements.